2021
DOI: 10.1111/odi.13852
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effectiveness of Ankaferd Blood Stopper® and Emdogain in periodontal regeneration

Abstract: Objectives The present study was performed to compare the effectiveness of Ankaferd Blood Stopper® (ABS) with enamel matrix derivatives (EMD) for treating fenestration defects in rats. Materials and Methods Forty‐eight male Wistar rats were randomly divided into six groups (each n = 8). Fenestration defects were created in all rats, to which ABS, EMD, or saline (S) was then applied. The rats were grouped and sacrificed at one of two different time points, as follows: ABS‐10‐group, ABS‐treatment/sacrifice on da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(87 reference statements)
0
0
0
Order By: Relevance
“…In an animal study, ABS application to bone defects was reported to histopathologically increase the formation of new bone in early bone healing while reducing the formation of inflammation and necrosis. 24 Guler et al 25 in a recent animal study have suggested that ABS may support early periodontal regeneration in fenestration defects. The antibacterial properties of this plant were thus proven.…”
Section: Discussionmentioning
confidence: 99%
“…In an animal study, ABS application to bone defects was reported to histopathologically increase the formation of new bone in early bone healing while reducing the formation of inflammation and necrosis. 24 Guler et al 25 in a recent animal study have suggested that ABS may support early periodontal regeneration in fenestration defects. The antibacterial properties of this plant were thus proven.…”
Section: Discussionmentioning
confidence: 99%